Caracterização funcional do mutante da ORF XAC1008 de Xanthomonas citri subsp. citri (Xac) - Santisteban, Angela Rocio Niño [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The production of frozen concentrated juice from sweet orange is an agricultural activity that is of great importance to Brazil, especially for the state of São Paulo. However, citrus canker is a disease that causes bigger losses to the Brazilian and global citrus industry, and to date there is no curative method for this disease and the main control is the eradication of infected plants. The citrus canker originated in Asia and its causal agent is the bacterium Xanthomonas citri subsp. citri (Xac), which attacks all commercial species of citrus. In a study of gene expression in two Xac mutants with impaired or total absence of symptoms of citrus canker, the ORF XAC1008 was highly expressed, so the aim of this study was the functional characterization of the protein encoded by ORF XAC1008 from Xac. The strategy used was the construction of a mutant of the ORF XAC XAC1008 and evaluation of its pathogenicity in plants of Rangpur lime (Citrus limonia Osbek) and sweet orange 'Pêra Rio' (Citrus sinensis (L.) Osbeck) compared with the wild isolate strain Xac 306. The technique used for obtaining the mutant was PCR-based site-directed mutagenesis using the suicide vector POK1, followed by homologous recombination. Pathogenicity tests of the mutant ΔXAC1008 showed that the mutation affected the color and shape of colonies, and prevent multiplication of bacteria in the plant, though it is still able to grow in the culture medium. The mutant decreased significantly biofilm formation and was not able to cause disease in sweet orange 'Pêra Rio' orange and Rangpur lime, two of its citrus hosts, while the wild isolate strain Xac 306 showed the characteristic symptoms of citrus canker in both hosts. The results indicate that the protein XAC1008 is not directly related to the virulence or pathogenicity of Xac in citrus but is essential for the proliferation and survival of the bacteria in the host. Although the presence of the ...

A produção de laranja e de suco concentrado é uma atividade agrícola que tem uma grande importância para o Brasil, em especial para o estado de São Paulo. Entretanto, o cancro cítrico é uma doença que causa grandes prejuízos à citricultura brasileira e mundial, sendo que até o momento não há nenhum método curativo para esta doença e o principal controle é a erradicação das plantas contaminadas. O cancro cítrico é originário da Ásia e tem como agente causal a bactéria Xanthomonas citri subsp. citri (Xac), a qual ataca todas as espécies comerciais de citros. Em um estudo de expressão gênica em dois mutantes de Xac que apresentavam diminuição ou ausência total de sintomas de cancro cítrico, a proteína XAC1008 se mostrou altamente expressa, pelo que o objetivo deste trabalho foi a caracterização funcional da ORF XAC1008 de Xac. A estratégia utilizada foi a produção de um mutante desta ORF e avaliação da sua patogenicidade quando comparada com a do isolado 306 de Xac selvagem em plantas de limão 'Cravo' (Citrus limonia Osbek) e laranja Pêra (Citrus sinensis (L.) Osbeck). A técnica utilizada para a obtenção do mutante foi a da mutagênese sítio-dirigida por PCR utilizando o vetor suicida pOK1, seguida de recombinação homóloga. Os ensaios de patogenicidade do mutante ΔXAC1008 mostraram que a mutação alterou a coloração e o formato das colônias e impediu a multiplicação da bactéria in planta, embora ela ainda seja capaz de crescer em meio de cultura. O mutante diminuiu de maneira significativa a formação de biofilme e não foi capaz de causar doença em laranja 'Pêra Rio' (Citrus sinensis (L.) Osbeck) e em limão 'Cravo' (Citrus limonia Osbek), dois de seus hospedeiros citros, enquanto que a Xac 306 selvagem apresentou os sintomas característicos do cancro cítrico nos dois hospedeiros. Os resultados indicam que a proteína XAC1008 não está diretamente relacionada...
Keywords: Cítricos - Doenças e pragas; Patogenicidade; Mutagenese; Cancro citrico; Bacterias fitopatogenicas; Mutagenesis